Analysis of Electability, Capacity, Campaign Resources on the Chances of Elected Public Officials in the General Election Democracy Party - Adams Cohen Robertson; Crenson Minnis; Hopkins Hogg; Jacob Son; Klandermans Clemen (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2022)
This research delves into the multifaceted landscape of electoral success by examining the intertwined influences of electability, capacity, and campaign resources on the performance of public officials from the Democracy party. By adopting a multidimensional approach, this study seeks to contribute to the understanding of how these factors interact and shape candidates' outcomes in general elections. Through a combination of quantitative analysis and qualitative insights, this research uncovers intriguing patterns in the electoral arena. Likability emerges as a powerful driver of voter choices, showcasing a robust positive correlation between candidates' likability scores and their electoral success. This underscores the significance of personal connection and emotional resonance in swaying voter decisions. Contrary to conventional wisdom, the study finds no significant correlation between candidate capacity attributes and electoral outcomes. While capacity remains valued, its impact appears contingent on its alignment with other factors such as likability and strategic resource allocation. This challenges traditional notions of experience as the primary determiner of electoral victory. The research further reveals a moderate positive correlation between effective campaign resource allocation and electoral success. Candidates who judiciously allocate resources, particularly in media coverage and social media engagement, tend to achieve better outcomes. This highlights the strategic importance of resource optimization in influencing voter perceptions and preferences. These findings provide a nuanced understanding of the complex interplay between electability, capacity, and campaign resources in the context of the Democracy party's electoral campaigns. The implications extend to strategic decision-making for the party, as well as contributing to the broader discourse on electoral dynamics and democratic representation. Looking ahead, this research suggests avenues for further exploration, inviting future studies to consider cross-cultural comparisons, technology's role, and the evolving nature of voter behavior in shaping electoral outcomes